2016
DOI: 10.1093/jac/dkv423
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and infection with extended-spectrum β-lactamase-producing Enterobacteriaceae in ICU patients: what impact on outcomes and carbapenem exposure?

Abstract: ESBL-PE infections increased carbapenem consumption, LOS and day 28 mortality. ESBL-PE infections were rather infrequent in carriers; however, even ESBL-PE carriage without infection increased carbapenem exposure and delayed discharge, thereby amplifying the selective pressure and the colonization pressure in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 37 publications
7
74
1
2
Order By: Relevance
“…Only 7% of ESBL-PE carriers developed ESBL-PE pneumonia in our study, in keeping with previous studies [15]. By comparison, in the 15-month period between January 2014 and the end of the study (March 2015), 49 (4%) of 1192 patients without ESBL-PE colonization developed ICUAP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Only 7% of ESBL-PE carriers developed ESBL-PE pneumonia in our study, in keeping with previous studies [15]. By comparison, in the 15-month period between January 2014 and the end of the study (March 2015), 49 (4%) of 1192 patients without ESBL-PE colonization developed ICUAP.…”
Section: Discussionsupporting
confidence: 91%
“…ESBL-PE carriage has been recently associated with higher carbapenem exposure than in non-carriers, even in the absence of infection [15]. Using carbapenem for all suspected pneumonia in ESBL-colonized patients may foster the emergence and spread of carbapenem-resistant bacteria [8, 23], which may in turn result in inappropriate therapy when secondary infection is caused by carbapenem-resistant non-fermenting gram-negative bacilli, as illustrated in our series in which most patients not having ESBL-PE infection essentially had P. aeruginosa infection, some of which were carbapenem resistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence is much higher than the 3.5% recently reported by Barbier et al [16], but the latter study was performed in a historical cohort (1996–2016) of 16,734 patients admitted to 17 French ICUs and ESBL prevalence has changed dramatically in the last two decades. Although we noted no relation between severity at admission and imported ESBL, Alves et al recently reported a lower rate of imported ESBL carriage of 8% in 308 patients with a much lower severity than in our population [17].…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, ESBLE carriage in otherwise uninfected critically ill patients has been associated with a three-fold increase in the empirical use of carbapenems during the ICU stay when compared to non-carriers [9]. Yet, documented absence of carriage might be used to withhold maximum broad-spectrum antibiotics in case of infection [10], and the development of rapid diagnostic tools-including phenotypic methods, mass spectrometry, or PCR-based assays-for earlier identification of pathogens and resistance patterns offers promising perspectives to target narrower-spectrum empirical therapy [6].…”
mentioning
confidence: 99%